The human story : where we come from and how we evolved - Lockwood, Charles (Sterling, 2008)
Created in association with London<U+2019>s Natural History Museum, this is a readable, up-to-date, well-illustrated, and user-friendly summary of the evidence as it stands today--Publisher description.